RELATIONSHIP OF PATIENT CHARACTERISTICS WITH THE SEVERITY OF COVID-19 IN HOSPITALIZED PATIENTS IN ROYAL PRIMA HOSPITAL MEDAN JANUARY- MARCH 2021 - Millenny Zai, Theodora Destry (JURNAL KEDOKTERAN RAFLESIA, 2021)
Coronavirus Disease 19 (COVID-19) is an infectious ailment as a consequence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Symptoms that get up due to SARS-CoV-2 infection are the most common with in the form of fever, fatigue, and dry cough, similarly to some of the symptoms and symptoms that patients may also moreover experience, are headache, conjunctivitis, sore throat, diarrhea, loss of sense of smell and skin rash. Serious signs can also additionally consist of issue respiration or shortness of breath, chest pain, and issue speak me or moving. Covid-19 is split into numerous types, specifically asymptomatic, mild, moderate, severe, and crucial that have a courting with affected person traits. This has a look at is a retrospective cohort have a look at. The general quantity of samples become 372 affected person clinical facts with information taken with inside the shape of age, gender, blood pressure, weight, height, Hb, urea, creatinine, SGOT, SGPT, blood glucose, smoking records, hypertension, coronary heart attack, kidney disorders, and radiological results. The results of this study showed that there were several patient characteristics related to the severity of Covid-19 (p<0.05), namely Body Mass Index (BMI), urea, GFR, X-Ray Radiology examination, CT-Scan examination, and the patient's initial symptoms. On the other hand, other characteristics did not show an association with the severity of Covid-19 (p>0.05), namely: age, gender, blood pressure, creatinine, SGOT, SGPT, Hb, blood glucose, smoking history, history of hypertension, history of heart attack, and history of renal impairment.Coronavirus Disease 19 (COVID-19) adalah penyakit menular yang disebabkan oleh Sindrom Pernafasan Akut Parah Coronavirus 2 (SARS-CoV-2). Gejala yang timbul akibat kontaminasi SARS-CoV-2 adalah yang paling umum berupa demam, kelelahan, dan batuk kering, serta beberapa gejala yang mungkin juga dialami penderita, yaitu sakit kepala, konjungtivitis, nyeri tenggorokan, diare, kehilangan indra penciuman dan ruam kulit.. Gejala serius yang dapat terjadi berupa kesulitan bernapas atau sesak napas, nyeri pada dada, dan kesulitan berbicara atau bergerak. Covid-19 dibedakan menjadi beberapa type yaitu tanpa gejala, ringan, sedang, berat, dan kritis yang memiliki hubungan dengan karakteristik pasien. Penelitian ini merupakan penelitian cohort retrospective. Jumlah sampel total berjumlah 372 rekam medis pasien dengan data yang diambil berupa usia, jenis kelamin, tekanan darah, berat badan, tinggi badan, Hb, ureum, kreatinin, SGOT, SGPT, KGD, riwayat merokok, hipertensi, serangan jantung, gangguan ginjal, dan hasil pemeriksaan radiologi. Pada hasil penelitian ini menunjukkan adanya beberapa karakteristik pasien yang berhubungan dengan derajat keparahan Covid-19 (p<0.05), yaitu Indeks Massa Tubuh (IMT), ureum, GFR, pemeriksaan Radiologi X-Ray, pemeriksaan CT-Scan, serta gejala awal pasien. Sebaliknya karakteristik lainnya tidak menunjukkan adanya hubungan dengan derajat keparahan Covid-19 (p>0.05), yaitu: umur, jenis kelamin, tekanan darah, kreatinin, SGOT, SGPT, Hb, KGD, riwayat merokok, riwayat hipertensi, riwayat serangan jantung, dan riwayat gangguan ginjal .